Cigarettes and Water Pipe Smoking Prevalence, Knowledge, and Attitudes Among the Palestinian Physicians in the West Bank - Hamzeh Al Zabadi; Samar Musmar; Ayah Hassouna; Doa'a Shtaiwi (SAGE Publishing, 2018)
Background: Tobacco use is one of the major public health threats nowadays. Smoking can affect everybody organ. Health professionals should play pivotal roles in tobacco control, and their attitude and practice toward tobacco use can affect the health of the community. Therefore, assessing and influencing physicians' attitudes and practice are one of the alternatives to reduce smoking prevalence in the community. We aimed to assess smoking status among medical physicians in the West Bank, Palestine to better understand their future role in any smoking cessation program. Material and methods: A cross-sectional study using the World Health Organization Global Health Professional Survey questionnaire was conducted. A non-probability sampling technique from a total of 6500 physicians registered in the Palestinian Medical Association in the West Bank was used. Results: The age ranged from 23 to 78 years with a mean of 34.92 years. Current smokers represented 60.3%. Of them, 18.5% were both cigarettes and water pipe smokers. The main reason that motivates the physician to smoke is experimenting (57.9%). Also stress (31.8%) and social pressure (26.4%) were of the most common causes to start smoking. Almost all medical doctors have a high level of knowledge regarding the health consequences of smoking. Smokers were less likely to hold favorable attitudes toward smoking cessation and support tobacco control policy compared with non-smokers ( P -values < .05). Conclusions: Physicians' degree of awareness and knowledge about their role in aiding patients to quit smoking are high. However, smokers' attitudes toward smoking cessation programs need to be improved to increase their involvement in such interventional programs.